Analisis Tahap Perkembangan Jiwa Beragama pada Anak: Studi Kasus Observasi Perilaku Ibadah - Amidatul Muna; Mutya Ula Nafi’ah; Linda Rahmawati (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2025)
The development of religious psychology in childhood has unique characteristics reflected in their worship behavior. This study aims to describe the worship behavior of an elementary school-aged child and analyze its alignment with the theory of children's religious development. This study employed a descriptive qualitative approach. The research subject was selected using a purposive sampling technique, involving a 10-year-old child and the parents as additional informants. The results indicated that the subject's worship behavior is still unreflective (imitative) and driven by parental external factors. However, the subject's concept of God as a "faceless light" and belief in the efficacy of prayer demonstrate an entry into the realistic stage. In conclusion, the subject's religious development is in a transition phase from the fairy tale stage to the realistic stage, which requires consistent environmental stimulation.